Features of physical education of students of higher educational establishments which have diseases of locomotorium - Humennyi V.S (Kharkov National Pedagogical University, 2012)
The methods of physical education of students which have diseases of locomotorium are considered. 184 students took part in research. The level of development of separate groups of muscles of students and loud speaker of exactness of motions is appraised. Co-ordinating capabilities are investigated by the computer system with the recreation of spatio-temporal parameters. It is recommended independent employments after physical education to conduct on the basis of individual tasks. It is marked that employments on the individual programs enable to even and pull up the least developed physical qualities to the statistically middle level. The author program is recommended on physical education. The program is instrumental in the increase of level of physical preparedness, warning of professional diseases and traumatism, achievement of high professionalism.